Discount usage in online sales : insights from a Portuguese retailer - Greef, Douwe de (2019)
Objectives – The objectives of this research are to evaluate the use of discounts in online sales to generate revenue and to identify factors that impact the use of discounts by consumers. Method – A very extensive dataset containing orders placed over the course of one year were analysed in order to identify significant predictors in discount usage. Findings – This research found that (1) being a first time shopper does not lead to a higher discount usage; (2) consumers who use more discounts are more likely to churn; (3) discount usage decreases as purchasing power increases; (4) while the value per order increases as the discount usage increases, the revenue per order decreases. Conclusions – In the current situation, discounts are not an effective tool to attract or retain customers, nor to increase revenue. Since these are typical goals for the use of discounts, the retailer should alter their strategy regarding price promotions in their online store.